Insight into Structural Features of Magnetic Kaolinite Nanocomposite and Its Potential for Methylene Blue Dye Removal from Aqueous Solution - Izzan Salwana Izman; Mohd Rafie Johan; Ruhaida Rusmin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
An in-depth understanding on the structural features of engineered magnetic adsorbent is important for forecasting its efficiencies for environmental clean-up studies. A magnetic kaolinite nanocomposite (MKN) was prepared using Malaysia’s natural kaolinite via co-precipitation method with a three different clay: iron oxide mass ratio (MKN 1:1, MKN 2:1 and MKN 5:1). The morphology and structural features of the magnetic composites were systematically investigated using techniques, such as: Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), surface area analysis (BET), Vibrating Sample Magnetometer (VSM), and zeta potential measurement. The removal efficiencies of the adsorbent for Methylene Blue (MB) dye were studied in batch method as a function of pH and initial concentration. MKN1:1 demonstrated the highest magnetisation susceptibility (Ms) of 35.9 emu/g with four-fold-increase in specific surface area as compared to the pristine kaolinite. Preliminary experiment reveals that all MKNs showed almost 100% removal of MB at low initial concentration (<50 ppm). The spent MKN adsorbent demonstrated an easy recovery via external magnetic field separation and recorded maximum adsorption capacity of 18.1 mg/g. This research gives an insight on the surface characteristics of magnetic clay composite for potential application as an effective and low-cost adsorbent in treating dye contaminated water. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).